2014
DOI: 10.1017/jfm.2014.455
|View full text |Cite
|
Sign up to set email alerts
|

Force acting on a square cylinder fixed in a free-surface channel flow

Abstract: We describe an experimental study of the forces acting on a square cylinder (of width b) which occupies 10-40 % of a channel (of width w), fixed in a free-surface channel flow. The force experienced by the obstacle depends critically on the Froude number upstream of the obstacle, Fr 1 (depth h 1 ), which sets the downstream Froude number, Fr 2 (depth h 2 ). When Fr 1 < Fr 1c , where Fr 1c is a critical Froude number, the flow is subcritical upstream and downstream of the obstacle. The drag effect tends to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 9 publications
(5 reference statements)
2
61
1
Order By: Relevance
“…Macabuag et al (2016a) is the only study to consider Froude Number as a TIM and found it to be a poor indicator of building damage when used alone, for the dataset considered. However, Froude Number is used to calculate the quasi-steady force discussed below (Qi et al, 2014;Foster et al, 2017), and recommend using different fragility curves for flow conditions characterized by high and low Froude numbers.…”
Section: Summary Of Intensity Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Macabuag et al (2016a) is the only study to consider Froude Number as a TIM and found it to be a poor indicator of building damage when used alone, for the dataset considered. However, Froude Number is used to calculate the quasi-steady force discussed below (Qi et al, 2014;Foster et al, 2017), and recommend using different fragility curves for flow conditions characterized by high and low Froude numbers.…”
Section: Summary Of Intensity Parametersmentioning
confidence: 99%
“…are the only empirical study to consider moment of momentum flux in their fragility curves. Note that nearly all current studies that consider force are using the standard drag equation (all except Macabuag et al (2016a), below, and who additionally consider moment of momentum flux), however, this does not account for alternative estimations, such as equivalent hydrostatic methods (MLIT, 2011), bore impact (Robertson and Riggs, 2011), or changes in flow regime (Qi et al, 2014;Foster et al, 2017). Macabuag et al (2016a) derived fragility functions using an equivalent quasi-steady force proposed by Qi et al (2014) and …”
Section: Summary Of Intensity Parametersmentioning
confidence: 99%
“…Froude number will be considered directly as a TIM (TIM6), and a force estimation which depends on the flow regime will also be considered (TIM7). TIM7 is an equivalent quasi-steady force proposed by Qi et al (2014) and suggested by Lloyd (2016) to represent the force of a tsunami inundation on buildings. It is evaluated via two different flow regimes determined by Froude number.…”
Section: Tsunami Inundation Simulation Datamentioning
confidence: 99%
“…The equations relate h, v and blockage ratio (building width/channel width) to the force, denoted here as F QS . Increasing the blockage ratio generally has the effect of increasing the force on the structure, and readers are referred to Qi et al (2014) for the calculation procedure. Defining an accurate blockage ratio for each building would require knowledge of the flow direction in order to define the cross section for which ''building width'' and ''channel width'' could be measured.…”
Section: Tsunami Inundation Simulation Datamentioning
confidence: 99%
See 1 more Smart Citation